Density functional theory investigation of surface defects in Sn-doped ZnO - C. Supatutkul (2018)
© 2016 . In this work, the first principle density functional theory calculation was used to investigate the Sn-doped ZnO on both non-polar (101(combining overline)0) and polar (0001) surfaces. The incorporation of Sn dopant in host material was modeled as ZnO with surface and bulk defects. The surface defect has Sn dopant substituting Zn site on the surface of structure. On the other hand, the bulk defect has Sn dopant substituting Zn site deep in the ZnO structure. The calculation of formation energy according to the thermodynamic growth conditions shows that the polar (0001) surface is less stable than the non-polar (101(combining overline)0) surface in a non-doped structure. However, when the ZnO structure is doped with Sn atoms, the polar (0001) surface reveals that its stability level is larger than that of the non-polar (101(combining overline)0) surface with bulk defect but is comparable to that of the non-polar (101(combining overline)0) surface with surface defect. Moreover, both defects yield the blue-shifted of the energy gap for non-polar (101(combining overline)0) surface, which suggests that the Sn-Doped ZnO is a potential alternative candidate for fabricating efficient transparent electrode application.